SIKAP DISIPLIN DAN TANGGUNG JAWAB TERHADAP PERILAKU BELAJAR ANAK DARI RUMAH SELAMA MASA PANDEMI - Ikhsan Gunadi; Asriana Kibtiyah (Al-Fikru : Jurnal Pendidikan Dan Sains, 2023)
The study from home policy during pandemic is thought to have an impact on changes in children's learning behaviour caused by a decrease in discipline and responsibility. The condition of houses with learning facilities and communication patterns were one of the factors that contributed to the decline. This study aims to determine whether there is a decrease in discipline and responsibility as well as children's learning behaviour while studying at home during the pandemic. With a quantitative approach, this research explores the data obtained. Data was collected using a Google Form questionnaire which was distributed to social media groups among parents/guardians of elementary school or madrasah primary school students in various cities in Indonesia. Data analysis used the t-test and F-test to determine the correlation of each variable. The results showed that there was a decrease in the attitude of discipline by 69 percent and a decrease in the attitude of responsibility by 64 percent. In addition, it also found (1) a significant effect between a decrease in discipline and a negative change in learning behaviour; (2) a significant difference between a decrease in the attitude of responsibility and a negative change in learning behaviour; and (3) there is a significant simultaneous effect between the decrease in discipline and responsibility with negative changes in learning behaviour.Keywords: Discipline, Responsibility, Learning Behavior, Pandemic Period